Breaking and making of olefins simultaneously using ozonolysis: application to the synthesis of useful building blocks and macrocyclic core of solomonamides - Kashinath, K.; Dhara, Santu; Reddy, D. Srinivasa (Organic Letters, 2015)
A simple and practical one-pot) two-directional approach to access olefinic esters through simultaneous breaking and making of olefins using ozonolysis of alkenyl aryl selenides is disclosed The scope of the method with a variety of example's is demonstrated, and the end products obtained here are useful building blocks. As a direct application of the present method,the macrocyclic cote of potent anti-inflammatory natural cyclic peptides, solomonamides, is synthesized.

Solution-phase synthesis of the macrocyclic core of teixobactin - Dhara, Santu; Gunjal, Vidya B.; Handore, Kishor L.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2016)
Towards the total chemical synthesis of the exceptionally potent antibiotic teixobactin, we synthesized the macrocyclic core of a natural product by using a solution-phase approach. The gramscale synthesis of L-allo-enduracididine and Shiina macrolactonization are highlights of the present disclosure.